ANALISIS KEKUATAN MATERIAL KOMPOSIT POLYESTER BERPENGUAT SERAT SISAL DAN SERBUK KAYU MAHONI DENGAN VARIASI FRAKSI VOLUME MATRIKS DAN REINFORCEMENT - Yoga Ahdiat Fakhrudi; Imam Basuki; Miftahul Ulum (Badan Penerbit Universitas Muria Kudus, 2026)
The purpose of this study is to examine how changing the volume percentage of sisal fiber and mahogany wood powder composites can improve their mechanical qualities. The hand lay-up method was used to create composites with a set resin volume fraction of 50% and varying volume fractions of sisal fiber and mahogany sawdust (30%:20%, 35%:15%, 40%:10%, 45%:5%, and 50%:0%). The tensile test (ASTM D638), bending test (ASTM D790), and impact test (ISO 179-1) were among the tests. According to the results, the best impact toughness (70.34 KJ/mm²) was achieved with a combination of 45% fiber and 5% powder. The composition with the maximum tensile strength (23.36 MPa), strain (0.041%), and elastic modulus (574.20 Pa) was 40% fiber and 10% powder; the composition with the highest bending strength (124.50 N/mm²) was 50% fiber and 0% powder. The best composition from the impact test—45% fiber and 5% powder—is used in this study's rearview mirror cover product.